Separation processes in the food and biotechnology industries : principles and applications - Grandison, A. S.; Lewis, M. J. 1949- (Woodhead Pub., 1996)
This book reviews recent methods and techniques for separating food components and products of the biotechnology industry. The introduction focuses on food composition and some of the conventional separation techniques. Subsequent chapters deal with each specific type or area of application individually and include information on the basic principles, industrial equipment available, commercial applications and an overview of current research and development. Contents include: Separation processes - An overview; Supercritical fluid extraction; Pressure-activated membrane processes; Ultrafiltration; Ion-exchange and electrodialysis; Innovative separation methods in bioprocessing; Fractionation in fat; Solids separation processes.
Keywords: Separation (Technology); Food -- Biotechnology.; Supercritical fluid extraction.; Ion exchange.; Ultrafiltration.; Electrodialysis.; elektronické knihy; electronic books